Hak-Hak Dari Pekerja Pkwt Yang Di PHK : (Analisis Putusan Pengadilan Hubungan Industrial Nomor 15/PDT.SUS-PHI/2020/PN Mtr.) - Abdi Haikal; Zaeni Asyhadie (Fakultas Hukum Universitas Mataram, 2023)
This research has the purpose to analyze the rights of the PKWT workers who get work termination and how the judge’s legal consideration when giving court decision in the Industrial court Decision Number 15/Pdt.Sus-PHI/2020/PN Mtr. This research uses normative-legal research. The approach method uses the statute approach, the conceptual approach, and the cases approach. The type of legal materials in this study uses primary legal materials, secondary legal materials, and tertiary legal materials. The legal materials are collected by a library study. The research analysis in this study uses qualitative legal analysis. Based on this research, the right of PKWT workers who get termination is based on the Industrial Court Decision Number 15/Pdt.Sus-PHI/2020/PN Mtr is not according to the positive law in Indonesia. In this case, Judges are only considering the juridical factors without considering the non-juridical factors.